2021
DOI: 10.1159/000513256
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Social and School Environment and Children’s Caries Experience Using Primary and Secondary Data: A Cluster Analysis

Abstract: Dental caries is still prevalent worldwide, even with advances in preventive and curative measures. The aim was to examine clustering patterns of socioeconomic and environmental characteristics of schools and their associations with caries experience of schoolchildren. An epidemiological survey with cross-sectional design was conducted in 2014/2015 and included 5,213 students (aged 2–11 years) from 38 public schools of Carapicuíba (SP, Brazil). Primary data consisted of dental examinations performed at schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The study included data from a large epidemiological survey of the municipality of Carapicuíba, carried out in 2014 and 2015, as previously described 15 . While the previous study focused on the relationship between sociodemographic variables and dental caries using an ecological design and school approach, the present study focused on individual characteristics of schoolchildren and the relation between caries experience, diet, access to oral health services, and oral hygiene habits.…”
Section: Methodsmentioning
confidence: 99%
“…The study included data from a large epidemiological survey of the municipality of Carapicuíba, carried out in 2014 and 2015, as previously described 15 . While the previous study focused on the relationship between sociodemographic variables and dental caries using an ecological design and school approach, the present study focused on individual characteristics of schoolchildren and the relation between caries experience, diet, access to oral health services, and oral hygiene habits.…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be considered that global targets in terms of absolute values are limited and, instead, health management and planning at local and national levels should formulate realistic goals for the oral health of each community. (17). The prevalence of children with caries in this sample was higher than that stipulated by the World Health Organization -WHO for the year 2000 in Latin America, whose objective was that 50% of children between 5 and 6 years old were free of caries.…”
Section: Resultsmentioning
confidence: 57%
“…In addition, there was a 3% increase in the odds of having cavities for each additional percentage of families living on up to minimum wage. (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been demonstrating that dental caries is still highly incident and prevalent in many regions of Brazil [38][39][40][41][42], therefore, it is necessary to identify the population and the risk factors involved with a higher occurrence risk in order to trace an efficient surveillance. Boing et al [36] have identified that dental caries has higher rates among the poorest individuals, and the identification of populations at higher risk may support interventional strategies to minimize the incidence of this condition [43].…”
Section: Discussionmentioning
confidence: 99%